Speech Disorders in Dysgnathic Adult Patients in the Field of Severity of Primary Dysfunction - Anna Lichnowska; Marcin Kozakiewicz (Applied Sciences, 2021)
The normative functioning of the stomatognathic system and masticatory apparatus requires specific coordination between several structures such as teeth with good occlusion, tongue without ankyloglossia or thrusting, and well-balanced facial muscles. This study aimed to evaluate the influence of non-normative primary functions such as breathing, swallowing, biting and chewing on the consonant pronunciation outcome in adults affected with facial skeletal deformities. Moreover, the authors would like to promote a new kind of speech therapy-orthognathic speech therapy. A total of 181 adults affected by skeletal class II and III malocclusion were included, along with the relationship between the malocclusion, speech deficiency (20 phonemes tested) and primary function disorders, in the subjects before and after surgical correction. The impact of surgery on pronunciation and primary function improvement and types of Polish phonemes most often misarticulated by Polish adults were also examined. Patients underwent combined treatment and received a full speech pathology examination. The treatment improved speech (p < 0.05), and primary functions (p < 0.05). Palatal, alveolar (p < 0.05), fricatives (p < 0.05), and labiodental consonant pronunciation (p < 0.05) improved. The surgical correction of malocclusion leads to better oral motor control and articulation of Polish consonants in adults.